Хүний эш (Төрөлөө зөв нэрлэцгээе) - Доржготов, Н. (Historia Mongolarum, 2003)
The Mongolian traditional human tree and all branches termins are first presented in this article. The author deals with the issue because of wrong translation common in movies where the two cousin "were married in that movie". The author corrected misinterpretation of some European termins and gave the Mongolian equivalents of European names.